Investigation of high‐pressure planetary ices by cryo‐recovery. II. High‐pressure apparatus, examples and a new high‐pressure phase of MgSO4·5H2O. Issue 3 (28th April 2018) - Wang, Weiwei; Fortes, A. Dominic; Dobson, David P.; Howard, Christopher M.; Bowles, John; Hughes, Neil J.; Wood, Ian G.
Abstract : An apparatus for the compression of materials to ∼2 GPa and subsequent rapid chilling to 80 K with extraction to ambient pressure is described. The partial resolution of a long‐standing problem concerning the high‐pressure phase behaviour of a water‐rich salt hydrate is demonstrated using the equipment. Abstract : An apparatus is described for the compression of samples to ∼2 GPa at temperatures from 80 to 300 K, rapid chilling to 80 K whilst under load and subsequent recovery into liquid nitrogen after the load is released. In this way, a variety of quenchable high‐pressure phases of many materials may be preserved for examination outside the high‐pressure sample environment, with the principal benefit being the ability to obtain high‐resolution powder diffraction data for phase identification and structure solution. The use of this apparatus, in combination with a newly developed cold‐loadable low‐temperature stage for X‐ray powder diffraction (the PheniX‐FL), is illustrated using ice VI (a high‐pressure polymorph of ordinary water ice that is thermodynamically stable only above ∼0.6 GPa) as an example. A second example using synthetic epsomite (MgSO4 ·7H2 O) reveals that, at ∼1.6 GPa and 293 K, it undergoes incongruent melting to form MgSO4 ·5H2 O plus brine, contributing to a long‐standing debate on the nature of the high‐pressure behaviour of this and similar highly hydrated materials. The crystal structure of this new high‐pressure polymorph of MgSO4 ·5H2 O has been determined at 85 K in space group Pna 21 from the X‐ray powder diffraction pattern of a sample recovered into liquid nitrogen and is found to differ from that of the known ambient‐pressure phase of MgSO4 ·5H2 O (pentahydrite, space group ), consisting of corner‐sharing MgO6 –SO4 ion pairs rather than infinite corner‐sharing chains.